Development and Performance Evaluation of Coir Pith Ash as Supplementary Cementitious Material in Concrete - Balagopal Venugopal; Viswanathan Sambamurthy (Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
India is the third largest producer of coconuts in the world after Indonesia and Brazil. The production of coconuts generates enormous volumes of by-products, which are dumped in landfills, causing issues like soil and air contamination, pollution of groundwater and other water bodies, with hazardous impacts on plant and animal life. Coir pith and short fibers are by-products from the coir industry obtained during the extraction of long fibers and account for approximately 70% of the mature coconut husk. Coir pith ash (CPA) was prepared by heating the dried coir pith in a metallic vessel at a temperature of 400 °C for 4 hours. The current paper shows an elaborate technical study on the material properties and performance of CPA in blended cements. The properties of concrete investigated were setting time, workability, compressive strength, splitting tensile strength, flexural strength and ultrasonic pulse velocity values. The specimens were tested at curing ages of 7, 28, 56 and 90 days. The test results indicated that CPA has moderate pozzolanic properties, with 10% as optimum replacement percentage.